Development of Malaysian wild bananas seed progenies, Musa acuminata ssp. malaccensis and Musa gracilis - Baruddin, Nurul Husna; Kayat, Fatimah (2015)
An embryo culture and micropropagation technique was done to develop the clonal population of wild bananas, Musa acuminata ssp. malaccensis and Musa gracilis for breeding purpose. The aim of this study was to compare in vitro germination and multiplication rate of two Malaysian wild bananas sp ecies. Embryos were cultured at different days; starting from day one until day 30 of fruit’s harvested. Result showed that the highest germination rate for both wild bananas was achieved from ripen fruit compared to unripe and over-ripen fruit. Germinated seedling were transferred onto MS media supplemented with 2 mg/L 6-benzylaminopurine (BAP) for several times to generate explants with multiple shoots. M. gracilis showed high proliferation rate compared to M. acuminata ssp. malaccensis after first sub cultured. In subsequent culture, number of shoots was increasing in M. acuminata ssp. malaccensis but not in M. gracilis.